EFFECT OF DIFFERENCES IN PLANTING DISTANCE ON GROWTH AND YIELD OF Zea mays in RED-YELLOW PODZOLIC SOIL - Desty Aulia Putrantri; Reza Zulfahmi; Hilman Hidayat; Hevia Purnama sari; Mustika Adzania Lestarit (J-PEN Borneo : Jurnal Ilmu Pertanian, 2023)
The problem that occurs in efforts to increase zea mays production is low land productivity, especially for red-yellow podzolic soil types. Setting plant spacing is an important factor to increase crop production easily and not increase production costs. Increasing the plant population per unit area can increase yields, but if the plant population continues to be increased, the yield will actually decrease. The aim of this research was to determine the response of growth and production of Zea mays to plant spacing treatments and to determine the correct planting distance with a high growth and production response. This research used a Randomized Block Design with 4 treatments, namely: P1 = planting distance 100 x 20 cm; P2 = planting distance 80 x 20 cm; P3 = planting distance 60 x 20 cm; and P4 = planting distance 40 x 20 cm; and repeated 3 times. Observation variables included plant height, ear weight, ear diameter, ear length, and sweetness level. The data analysis used was analysis of variance to determine whether the treatments were significantly different or not and continued with the LSD test with a significance level of 5%. The research results showed that differences in the planting distance of Zea mays on red-yellow podzolic soil had an effect on plant height, cob weight without corn husks, cob weight with corn husks, and cob length. Treatments P1 and P2 were the best treatments for the variables plant height, cob weight without corn husks, and cob weight with corn husks. Meanwhile, for the cob length variable, the best treatment is the P1 treatment.